2020
DOI: 10.1007/s00415-020-10199-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the COVID-19 pandemic on acute stroke reperfusion therapy: data from the Lyon Stroke Center Network

Abstract: Background The coronavirus disease 2019 (COVID-19) pandemic would have particularly affected acute stroke care. However, its impact is clearly inherent to the local stroke network conditions. We aimed to assess the impact of COVID-19 pandemic on acute stroke care in the Lyon comprehensive stroke center during this period. Methods We conducted a prospective data collection of patients with acute ischemic stroke (AIS) treated with intravenous thrombolysis (IVT) and/or mechanical thrombectomy (MT) during the COVI… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 15 publications
3
20
0
Order By: Relevance
“…Diegoli et al [ 16 ] analyzing a population-based stroke registry in Joinville, Brazil, found 36.4% reduction in stroke admissions upon initiation of lockdown measures in 2020 compared to the equivalent time in 2019 with no difference in admissions for severe stroke defined as NIHSS >8, ICB, and SAH. These findings may also be local phenomenon as shown by a publication of the Lyon Stroke Center network and the combined descriptive data of 4 German university stroke units by Hoyer et al [ 2 , 38 ]. The latter group showed a significant decrease in the number of admissions for TIA in 3 of 4 centers upon the lockdown by 85% and a reduction of stroke admission to 46% in 2 of 4 centers.…”
Section: Discussionmentioning
confidence: 80%
“…Diegoli et al [ 16 ] analyzing a population-based stroke registry in Joinville, Brazil, found 36.4% reduction in stroke admissions upon initiation of lockdown measures in 2020 compared to the equivalent time in 2019 with no difference in admissions for severe stroke defined as NIHSS >8, ICB, and SAH. These findings may also be local phenomenon as shown by a publication of the Lyon Stroke Center network and the combined descriptive data of 4 German university stroke units by Hoyer et al [ 2 , 38 ]. The latter group showed a significant decrease in the number of admissions for TIA in 3 of 4 centers upon the lockdown by 85% and a reduction of stroke admission to 46% in 2 of 4 centers.…”
Section: Discussionmentioning
confidence: 80%
“…First, consistent with prior reports, 14 we found that the rates of STA in our EDs dramatically decreased during the pandemic by 54%. Reports around the world vary in the magnitude of this effect based on geographical location and timing of reporting: 9–40% in France, 9 , 15 23–28% in Spain, 4 24–31% in Scandinavia, 16 25% in California, 17 32% in neighboring Ontario (Canada), 18 40% in China, 5 , 14 and 30–46% in New York. 19 These observations are a direct consequence of the implementation of stay-at-home orders and lockdowns enforced by local and federal governments.…”
Section: Discussionmentioning
confidence: 99%
“…No significant difference was observed in the onset-to-door time between the two groups (p = 0.97), whereas an almost significant difference was observed in the door-to-picture time (p = 0.08). The median door-to-picture time did not differ significantly between patients who were diagnosed using CT (15 [10][11][12][13][14][15][16][17][18][19][20][21] vs. 14 [9][10][11][12][13][14][15][16][17][18][19][20][21] min, p = 0.24) (Fig. 3A).…”
Section: Resultsmentioning
confidence: 99%